Spoleczny system produkcji w Niemczech - model na przyszlosc? - Michal Moszynski (Institute of Economic Research (IER), 2015)
– The concept of social system of production is one of the research perspectives by which the institutional arrangements of modern market economies are being analyzed. On this basis considerations can be made on distinctive arrangements in given countries, in line with the thesis of Variety of Capitalism approach, as well as explorations can be undertaken of issues of sustainability of institutional configurations and of the complementarity of their components. The study raises these issues in theory and carries out their preliminary verification on the example of Germany's social system of production, with special regard to the labor market. Based on the critical literature review a set of specific features of the German model was selected, as proposed by the concept of the social system of production, divided in four main categories: institutions, organizations, social values and economic policy. Then, using a secondary statistical data and qualitative analysis, the trends affecting these elements are identified, in order to verify the thesis of complementarity and the stability of the German social production system.
Keywords: J40; J52; L16; L23; P17; 330; Germany; labour market; institutions; social production system